Real-time estimation of power margin from on-line data accumulated through localized measurements - Faruque, M.O.; Moghavvemi, Mahmoud (CRL Publishing, 2004)
This paper proposes a technique to associate maximum power transfer theory and system stability via the computation of real and reactive power limits of transmission lines. The difference of computed maximum power and instantaneous load can be defined as the power margin of a specific transmission line at that instant. The maximum power transfer capability can reflect stability limits of particular transmission lines. Furthermore, the proposed method can be employed to calculate critical power that a particular node or bus can endure without collapsing. Solutions to complex mathematical derivations using Jacobian matrices, eigen-values or load flow are not required. Hence fast and accurate solutions for the evaluation of transmission lines and bus stability can be obtained. Furthermore, the power margin is calculated in terms of MW or MVAr. Tests were carried out on the IEEE Test Bus System. Tests results have confirmed that the maximum power transfer capability of each line varies with changes in the bus voltage, power factor of the power transferred through the line and the transmission line parameters, therefore, this technique is most suitable for on-line monitoring of system stability.